Q: Replace 7 for x and evaluate the expression 9x - 2x?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

It's 9 x 7 minus 2 x 7. So its 63 - 14.

The expression simplifies to: -7x-4

It can be simplified to: 9y-2x

2x + 9x simplified would be 11x

2x + 24 = 9x - 39= 2x + 63 = 9x= 63 = 7x= x = 9

Related questions

X = 7 9x - 2x = 49

It's 9 x 7 minus 2 x 7. So its 63 - 14.

6x - 7

The expression simplifies to: -7x-4

the new problem would be 9(7)-2(7) when you substitute 7 for x.The answer is 63-14= 49 So your answer is 49(:

It can be simplified to: 9y-2x

2x + ? = 9x9x - 2x = 7xso...2x + 7x = 9x

16

2x + 9x simplified would be 11x

2x + 24 = 9x - 39= 2x + 63 = 9x= 63 = 7x= x = 9

2x + 5x - 1 = 9x 7x - 1 = 9x -1 = 9x - 7x -1 = 2x -1/2=x

9x-5x-2x = -4 2x = -4 x = -2